2003
DOI: 10.1097/01.brs.0000097890.96524.a1
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Back-Café Concept to Rehabilitation After Lumbar Spinal Fusion: A Randomized Clinical Study With a 2-Year Follow-Up

Abstract: The patients in the back-café group were significantly better at accomplishing a succession of daily tasks compared with the video and training groups 2 years after lumbar spinal fusion. At the 2-year follow-up the training group had a significant pain problem compared with the video and back-café groups. The video group had significantly more treatment demands outside the hospital system. This study demonstrates the relevance of the inclusion of coping schemes and questions the role of intensive exercises in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 32 publications
3
118
1
4
Order By: Relevance
“…In addition to our own observations in a randomised controlled trial [2], a previous study showed the importance of post-operative rehabilitation for the outcome of lumbar fusion [4]. In both trials, biopsychosocially orientated rehabilitation was more effective than exercise therapy in improving functional outcome [2,4].…”
Section: Introductionsupporting
confidence: 56%
“…In addition to our own observations in a randomised controlled trial [2], a previous study showed the importance of post-operative rehabilitation for the outcome of lumbar fusion [4]. In both trials, biopsychosocially orientated rehabilitation was more effective than exercise therapy in improving functional outcome [2,4].…”
Section: Introductionsupporting
confidence: 56%
“…To imitate the session structure in the exercise group and thereby the potential effect of being in a group [25], patients met in a 'café-like' environment which provided the opportunity to exchange personal experiences of pain and physical incapacity. They met in groups of up to a maximum of 10 people once every second week for 10 weeks for a session of 45 minutes where they engaged in unstructured talk with a physiotherapist present.…”
Section: Methodsmentioning
confidence: 99%
“…There is widespread agreement throughout this literature that patients do not know what they should or should not do during recovery from surgery [7,18] There is little evidence for any post-operative restrictions (Table 1). There is strong evidence that activity is not harmful, together with theoretical arguments and considerable circumstantial evidence that progressive activity is beneficial (Table 2).…”
Section: Literature Reviewmentioning
confidence: 99%